Perception of nurses regarding family needs of critically ill patients in a tertiary hospital of Kathmandu: A cross-sectional study - Pandey, Sabita; Shrestha, Roshanee; Paudel, Narayani (Journal of Kathmandu Medical College, 2019)
Background: Getting serious illness and being admitted in critical care unit is always stressful to patient and family members. Meeting the needs of family members of patients in the intensive care unit is a primary responsibility of intensive care unit staff and an important criterion in assessment of quality of care. Objectives: The aim of this study was to assess the family members’ needs of critically ill patients as perceived by nurses. Methodology: A descriptive cross sectional study was conducted among 50 nurses from different critical care units of Kathmandu Medical College Teaching Hospital using purposive sampling technique. Structured questionnaire was developed by referring to “Critical Care Family Needs Inventory”in our context for data collection and collected data was analyzed by using Statistical Package for Social Sciences version 16. Results: The mean age of the respondents was 24.98 ± SD 2.77.Regarding education and experience, 58% respondents had proficiency certificate level and 42% had bachelor level education and mean working experience in critical care unit was 37.54 months. Regarding the importance of family needs, 86% nurses perceived “explanation about the critical care unit environment before admitting the patient in critical care unit” as very important need for the relatives. Likewise, 58% nurses perceived “to know which staff members could give what type of information” and “to be alone at any time” as the least important needs. Conclusion: The study found that clear explanation about the critical care environment to the relatives is very important to gain co-operation from them in treatment of critically ill patients. Hence, staff of critical care unit needs to be aware in meeting the needs of relatives.